Kinematic Strategies for Hyoid Movement in Rapid Sequential Swallowing. - Chi-Fishman, Gloria; Sonies, Barbara C. (Journal of Speech, Language & Hearing Research, 2002)
Past videofluoroscopic and EMG evidence has shown that rapid sequential swallowing differs from discrete swallows, but our knowledge of the control strategies remains incomplete. This study examined in detail the interrelationships among kinematic variables to discern the strategies for deglutitive hyoid motion during discrete (5 cc, .10 cc, 20 cc, 30 cc) and rapid sequential (120 cc) swallowing tasks. Submental ultrasound was conducted with head and transducer stabilization on 30 healthy subjects (15 males, 15 females) in three age groups (20-39, 40-59, 60-79 yrs). Frame-by-frame changes in hyoid position were tracked from digitized images of 236 discrete and 318 rapid sequential swallows. Repeated-measures analyses of variance were conducted on a number of kinematic variables with corrections for multiple tests and comparisons. The main effect of task was significant for all variables except forward peak velocity. Per post hoc contrasts, rapid sequential swallows had significantly reduced maximal amplitude (maximal displacement), total distance, backward peak velocity, at-max and total durations, and time to backward peak velocity in comparison with discrete swallows of any volume. Amplitude “down-scaling” was the prominent kinematic strategy used to accomplish rapid sequential swallows in a shorter time while keeping forward peak velocity essentially unchanged. In contrast, amplitude “up-scaling” was the strategy for accommodating larger-volume discrete swallows. Our results confirm built-in flexibility in the functional range of deglutitive hyoid motion. Reprinted by permission of the publisher.